Photocatalytic Degradation of Trifluralin in Aqueous Solutions by UV/S2O82− and UV/ZnO Processes: A Comparison of Removal Efficiency and Cost Estimation - Fatemeh Sadeghi; Abdolmajid Fadaei; Fazel Mohammadi-Moghadam; Sara Hemati; Gashtasb Mardani (International Journal of Chemical Engineering)
Trifluralin is one of the most widely used herbicides, being accounted as the cause of cancer in human. In the present research, the UV/S2O82− and ZnO/UV processes’ efficiency in the removal of trifluralin was investigated. A lab scale equipped with a UV lamp was applied. The parameters were studied, including initial trifluralin concentration (0.4–1.2 mg/L), contact time (20–60 min), S2O82− concentration (20–60 μM), and ZnO concentration (50–150 mg/L). The remained trifluralin concentration was measured by HPLC. This study proved the trifluralin removal of 92.90 ± 1.6% and 87.91 ± 19.22% for UV/S2O82− and UV/ZnO processes in the best operation conditions (contact time of 60 min, the persulfate concentration of 40 μM, and the ZnO concentration of 100 mg/L). The optimal trifluraline concentrations were 1.2 mg/L and 0.6 mg/L for UV/S2O82− and UV/ZnO processes, respectively. In both processes, the removal efficiency of trifluralin increased significantly with increasing contact time. The findings exhibited that both processes UV/S2O82− and UV/ZnO followed the zero-order kinetic. The electrical energy consumed of UV/S2O82 and UV/ZnO was about 43.95 and 20.41 Kwh/kg, respectively. The results show that UV/S2O82− and ZnO/UV processes were appropriate as the effective treatment method for trifluralin removal. Therefore, it is proposed to study the performance of these processes as an environmentally friendly practice in full scale with real wastewater.